A Study of Compost Added to a Casing Technique in Agaricus bisporus Cultivation from Phase III Bulk Compost - Zied, Diego Cunha [UNESP]; Almeida Minhoni, Marli Teixeira [UNESP]; Emilio Pardo-Gonzalez, J.; Pardo-Gimenez, Arturo (Amer Soc Horticultural Science, 2010)
The aim of this study was to assess the effect of the addition of different rates of colonized compost and formaldehyde treatment on production parameters (yield, biological efficiency, mushroom number, mushroom weight, and earliness) in a Dutch commercial casing using Phase III bulk compost as a base substrate for growing Agaricus bisporus. Four rates of spawn-run compost (0 g.m(-2), 200 g.m(-2), 400 g.m(-2), and 600 g.m(-2)) and formaldehyde treatment (with or without) were used. The experiment was designed as a double factorial in a randomized complete block design. Each block contained six replicates per treatment (a compost bag with 20 kg). The compost added to casing (CACing) technique when applied properly and combined with the use of Phase III compost had significant benefits, including increased mushroom yield, weight, and reduced the growing cycle, especially with the rate of 600 g of spawn-run compost/m(2) of casing. on the other hand, the application of formalin reduced yield with or without the CACing technique, which implies the need for an alternative treatment for disinfection. An alternative method may either be thermal or chemical treatments to the casing such as using formaldehyde before mixing the casing with spawn-run compost and before the addition of casing above the colonized compost.
Keywords: mushrooms industry; yield; earliness; technology process